Comparing alcohol screening measures among HIV-infected and -uninfected men. - McGinnis, Kathleen A; Justice, Amy C; Kraemer, Kevin L; Saitz, Richard; Bryant, Kendall J; Fiellin, David A (Alcoholism, clinical and experimental research, 2013)
Brief measures of unhealthy alcohol use have not been well validated among people with HIV. We compared the Alcohol Use Disorders Identification Test (AUDIT) to reference standards for unhealthy alcohol use based on 30-day Timeline Follow Back (TLFB) and Composite International Diagnostic Interview-Substance Abuse Module (CIDI-SAM), among 837 male HIV-infected and -uninfected patients in the Veterans Aging Cohort Study.
Keywords: Adult; Alcoholism; Cohort Studies; HIV Infections; Humans; Male; Mass Screening; Middle Aged; Prospective Studies; Questionnaires